2015
DOI: 10.1016/j.bpj.2015.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Arresting Amyloid with Coulomb’s Law: Acetylation of ALS-Linked SOD1 by Aspirin Impedes Aggregation

Abstract: Although the magnitude of a protein's net charge (Z) can control its rate of self-assembly into amyloid, and its interactions with cellular membranes, the net charge of a protein is not viewed as a druggable parameter. This article demonstrates that aspirin (the quintessential acylating pharmacon) can inhibit the amyloidogenesis of superoxide dismutase (SOD1) by increasing the intrinsic net negative charge of the polypeptide, i.e., by acetylation (neutralization) of multiple lysines. The protective effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
93
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(100 citation statements)
references
References 61 publications
(79 reference statements)
4
93
3
Order By: Relevance
“…[1,4] Deoxyribonuclease and ovalbumin, for example, have identical isoelectricp oints of pI = 5.1, but the formal and measured net charge of both proteins differ by approximately 7u nits at pH 8.4. [4] The systematic absence of experimentally determinedv alues of Z has likely impeded ar igorous understanding of most chemicalp rocesses in which proteinsa re involved including aggregation and self-assembly, [20][21][22][23][24][25][26] ligand binding, [27][28][29][30][31][32][33][34] catalysis, [35][36][37][38][39] electron transfer, [3,6,[40][41][42][43][44][45][46][47] protein crystallization, [14,48] analytical separation, [49,50] and protein engineering. [51][52][53][54][55][56] It is tempting to assume that the formal net chargeo faprotein predicted from generalized residue pK a values (Z seq )issosimilar to the actual net charge that any difference is irrelevant, and the isoelectric point tells us all we need to know about ap rotein's net charge.…”
Section: Introductionmentioning
confidence: 99%
“…[1,4] Deoxyribonuclease and ovalbumin, for example, have identical isoelectricp oints of pI = 5.1, but the formal and measured net charge of both proteins differ by approximately 7u nits at pH 8.4. [4] The systematic absence of experimentally determinedv alues of Z has likely impeded ar igorous understanding of most chemicalp rocesses in which proteinsa re involved including aggregation and self-assembly, [20][21][22][23][24][25][26] ligand binding, [27][28][29][30][31][32][33][34] catalysis, [35][36][37][38][39] electron transfer, [3,6,[40][41][42][43][44][45][46][47] protein crystallization, [14,48] analytical separation, [49,50] and protein engineering. [51][52][53][54][55][56] It is tempting to assume that the formal net chargeo faprotein predicted from generalized residue pK a values (Z seq )issosimilar to the actual net charge that any difference is irrelevant, and the isoelectric point tells us all we need to know about ap rotein's net charge.…”
Section: Introductionmentioning
confidence: 99%
“…To accelerate amyloidogenesis and reduce stochasticity ( 9 ), solutions are gyrated in microtiter plates at >100 rpm with millimeter-sized stirring beads placed in each sample well ( 9 , 12 , 13 ). Beads are typically composed of polytetrafluoroethylene (Teflon), but borosilicate glass and polymethylmethylacrylate (PMMA) have also been used ( 8 , 9 , 12 , 14 , 15 , 16 ). Establishing a few basic rules of thumb for how different bead types do or do not affect formation rates (and morphologies) of amyloid fibrils will help optimize assays; help discern the growing (and often inconsistent) list of reported rates of amyloid nucleation and elongation ( 10 , 14 , 17 , 18 ), and might uncover clues about the mechanical, chemical, and surface forces that drive fibrillization.…”
Section: Introductionmentioning
confidence: 99%
“…Abdolvahabi and co-workers demonstrated that acylation of Lys residues in superoxide dismutase 1 with aspirin increases the net negative charge of the polypeptide and slows the rate of aggregation. 50 In a similar fashion, Patil and Alexandrescu have recently applied a charge repulsion approach to inhibiting amylin self-assembly by preparing “charge-loaded” analogs of full-length amylin. 51 In this study, strings of Arg or Asp residues were strategically incorporated into the native amylin sequence to produce aggregation inhibitors.…”
Section: Resultsmentioning
confidence: 99%